Proceedings of the 19th ACM Conference on Computer-Supported Cooperative Work &Amp; Social Computing 2016
DOI: 10.1145/2818048.2819939
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Volunteer Engagement in Humanitarian Mapping

Abstract: Organisers of large-scale crowdsourcing initiatives need to consider how to produce outcomes with their projects, but also how to build volunteer capacity. The initial project experience of contributors plays an important role in this, particularly when the contribution process requires some degree of expertise. We propose three analytical dimensions to assess first-time contributor engagement based on readily available public data: cohort analysis, task analysis, and observation of contributor performance. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…The second-most frequent predictive factor was disaster _campaiдn, controlling for the particular recruitment effects during event-centric disaster campaigns which can yield lower average newcomer retention [12]. Both support the general expectation in the literature that intrinsic motivation is one of the strongest predictors for future participation [6,9,11,28]. Two further aspects related to peer feedback were found to have a powerful effect on newcomer retention: the use of verbal rewards in validation messages, and feedback that was sent without much delay.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The second-most frequent predictive factor was disaster _campaiдn, controlling for the particular recruitment effects during event-centric disaster campaigns which can yield lower average newcomer retention [12]. Both support the general expectation in the literature that intrinsic motivation is one of the strongest predictors for future participation [6,9,11,28]. Two further aspects related to peer feedback were found to have a powerful effect on newcomer retention: the use of verbal rewards in validation messages, and feedback that was sent without much delay.…”
Section: Discussionmentioning
confidence: 58%
“…HOT is a volunteer platform which provides maps for regions in humanitarian need, it seeks to grow a vast contributor community so it can better cover the vast scales of affected geographic regions. While participation is online and open to the public, volunteers need to learn specialist tools and workflows in order to contribute, and many newcomers drop out early [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel initiatives in response to the Ebola pandemic in 2014-2016 include hackathons organized in western capitals to map resources for West African response, and western non-governmental organizations (NGOs) that provide communication-based outbreak models to multinational humanitarian organizations (Sangokoya 2014;Moore 2015;Dittus et al 2016) or build geographic information system (GIS) maps for national authorities (Timo Lüge 2014). Early work is even underway to develop artificial intelligence responses to combat the spread of infectious diseases, by using multiple sources of publically available data to algorithmically predict the appearance and spread of disease (Barron 2014).…”
Section: Diagnosticsmentioning
confidence: 99%
“…There is some evidence that communal event settings can play an important role in fostering sustained contributor activity. In a recent study of HOT contributor engagement, it was found that mapping initiatives which organised mapathons had higher newcomer retention rates [7], however it is not yet known whether this can be attributed to the mapathon format itself.…”
Section: Introductionmentioning
confidence: 99%